Strengthening capacity in climate adaptation. Training toolkit and use case - Accelerating Impacts of CGIAR Climate Research for Africa (Accelerating Impacts of CGIAR Climate Research for Africa, 2023)
This training resource kit aims to support multi-stakeholder platforms and consortia at landscape level that aim to strengthen capacities for climate smart strategies and actions in food and agriculture. The training kit provides an introduction to a diversity of science-based tools and processes that can support climate smart approaches as well as practical support in how to collaboratively learn from each other in the process and co-create a roadmap for capacity strengthening in climate adaptation. The training kit has been developed by AICCRA in collaboration with the Central Highlands Ecoregion Foodscape (CHEF).CHEF is an integrated landscape initiative with a multistakeholder group, operating at landscape level in the Central Highlands in Kenya and is part of a global set of foodscapes initiated by The Nature Conservancy. CHEF brings together producer associations, water use associations, community conservancies, county governments, NGOs, private sector businesses, researchers, and other, to transition to regenerative food systems. In a partnership, the AICCRA and CHEF programs co-designed a two-day collaborative learning workshop on Climate adaptation in the Central Highlands on October 4 and October 5, 2023.